Drinking, smoking, and other drugs - Haughton, Emma (Austin, Tex. : Raintree Steck-Vaughn Publishers, 2000)
Explains the nature of drugs, both legal and illegal, how they can affect the body, and how they can help or harm users.
Includes bibliographical references and index.
Keywords: Drugs -- Juvenile literature; Substance abuse -- Juvenile literature; Drugs; Drug abuse